Christian Ethics, Lutheran Tradition, and Pluralistic Society - Nikolajsen, Jeppe Bach (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2020)
In the Lutheran tradition, the particular aspects of theological ethics have often been overlooked, if not outright denied. Thus, it is not uncommon for Lutheran theologians to emphasize the universal aspects of theological ethics and to downplay its particular aspects, even to the point of arguing that a Christian ethics does not exist. Against this background, the article gives several arguments for drawing Lutheran ethics in a direction that will allow its particular aspects to be more clearly articulated. It also presents certain features of Luther’s ethical position that might foster an understanding of the particular aspects of Lutheran ethics. Building on this, the article points to a contemporary Lutheran position of relevance to a pluralistic society.